A Comparative Survey of Female Figures in Persian Miniatures: Studying Form, Color and Content of Miniatures by Moein Mosaver and Hosein Behzad - Elham Khatiri; Behnam Zangi; Fatemeh Fakharan (Journal of Visual Art and Design, 2023)
Moein Mosaver and Hosein Behzad depicted beauty in the form of female figures using their unique ways of applying form, color, and content. The purpose of the present research was to study the way female figures are drawn in works of Mosaver and Behzad, compare them, and find out the relationship between them to finally answer the main research question, which concerns finding the similarities and differences between the works of both artists in form, color, and content. The method of the research was qualitative, the way the data was processed was descriptive-analytic, and the information was gathered through library sources. Regarding the time gap between the lives of saver and Behzad, it seems there should be similarities and differences between their miniatures. The results of the research showed that the composition in the works of both artists is mostly vertical and centralized, and the primary color blue and the secondary colors green, purple, and orange are mostly used. Foreign influences and the impact of the economic conditions are obvious in their works. Some of the differences between their works are the application of more primary and warm colors in Mosaver’s works and less variety of color in Behzad’s, while the latter’s lines are freer. Behzad also used perspective in his miniatures, and he preferred content over form.